Experimental and Analytical Studies of String Steel Structure for Bridges - Edmundas Beivydas; Algirdas Juozapaitis; Ilze Paeglite (The Baltic Journal of Road and Bridge Engineering)
Due to their efficiency, suspension structures are widely used in both roof slabs and different kinds of bridges, from which stress ribbon pedestrian bridges can be distinguished. The main disadvantage of the latter is high deformability, especially under asymmetrical loads. Recently, string structures or their systems have been introduced into bridge building. Numerical and experimental analysis of string behaviour under symmetrical and asymmetrical loads is carried out in the article. Analytical expressions for the calculation of string displacements and tensile forces are presented. The impact of the string pre-stress on the state of its stresses and deformations was evaluated. The assessment of the accuracy of analytical expressions by applying the results of numerical and experimental research is presented. A methodology is proposed for calculating the pre-stressing force taking into account the operational requirements. Three main loading options at different string pre-stress values are analysed. It is worth mentioning that the difference (error) between the analytical and numerical results is not extensive, it does not exceed 3%. It is necessary to notice that in all cases, the analytically obtained results are somewhat higher than FEM (numerically) obtained results.